THE FORMATION OF SOCIAL AND VOLUNTEER PROJECTS WITH THE INVOLVEMENT OF PR EVENTS IN MODERN CONDITIONS - BLYZNYUK, Tetyana; MAISTRENKO, Olga; KINAS, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In today's environment, we face numerous social problems, such as poverty, unemployment, environmental disasters, discrimination, health and education problems. These problems need immediate solutions because they affect the quality of life of millions of people around the world. Social volunteer projects are becoming key initiatives aimed at overcoming these challenges, as they involve citizens in active participation in solving problems that directly affect them. Volunteering is the basis of civil society, as it contributes to the development of social cohesion, mutual support and solidarity. Volunteers play an important role in providing assistance to those who need it, in creating joint projects and initiatives aimed at improving living conditions in communities. Volunteer initiatives also contribute to the development of civic consciousness and activism, which is extremely important for building a democratic and just society. PR events are an integral part of the successful implementation of social and volunteer projects. They make it possible to draw attention to the problems that are solved within the framework of the project, to attract new volunteers and partners, to increase the level of public awareness of the project and its purpose, as well as to ensure support from the public and the media.PR events help draw attention to social volunteer projects and the problems they solve. PR events and event management in general are an effective means of attracting new volunteers and partners to social and volunteer projects. Through events such as information campaigns, open days, trainings and seminars, project organizers can present their activities, attract new participants and secure support from businesses, public organizations and other partners.Digital technologies open up new opportunities for PR events and audience involvement in social and volunteer projects. Social networks, mobile applications, online platforms allow you to quickly and effectively spread information, attract new participants, coordinate the activities of volunteers and increase the effectiveness of projects. However, it also requires organizers to acquire new skills and knowledge in the field of digital communications.The modern world is constantly changing, and social volunteer projects must be flexible and adapted to new conditions. This includes taking into account changes in social needs, technological innovations, socio-economic conditions and other factors. It is important to be ready for a quick response to new challenges and opportunities that appear in the process of project implementation.Social volunteer projects involving PR events have great potential for creating positive changes in society and improving the living conditions of the community. The effective use of PR tools allows you to raise the level of awareness of problems, attract more participants and resources, as well as ensure the successful implementation of such projects in modern conditions.
Keywords: project; social project; volunteering; PR events; events; event management; grants